2012
DOI: 10.1016/j.jtcvs.2011.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Restricted cusp motion in right-left type of bicuspid aortic valves: A new risk marker for aortopathy

Abstract: In the bicuspid aortic valve commonly defined as normofunctional by echocardiographic criteria, restricted systolic conjoint cusp motion causes flow deflection. The novel measurement introduced can quantify restricted cusp opening, possibly assuming prognostic importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
76
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 25 publications
(54 reference statements)
8
76
0
Order By: Relevance
“…In a small, selected cohort of patients with morphologically and functionally 'homogeneous' BAVs, all right-coronary-left-coronary type, all non-stenotic and non-regurgitant, the cusp opening angle (COA, between the long-axis section of the central part of the fused leaflet and the ventricular-aortic junction plane, in systole), was significantly narrower than in matched tricuspid aortic valve (TAV) of healthy subjects, showing a significant correlation with the yearly aortic growth rate in subsequent prospective follow-up [1], thus proving to be a promising tool for prognostic stratification. Since then, we have expanded that cohort, confirming the results also in the right-coronary-noncoronary type of BAV.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…In a small, selected cohort of patients with morphologically and functionally 'homogeneous' BAVs, all right-coronary-left-coronary type, all non-stenotic and non-regurgitant, the cusp opening angle (COA, between the long-axis section of the central part of the fused leaflet and the ventricular-aortic junction plane, in systole), was significantly narrower than in matched tricuspid aortic valve (TAV) of healthy subjects, showing a significant correlation with the yearly aortic growth rate in subsequent prospective follow-up [1], thus proving to be a promising tool for prognostic stratification. Since then, we have expanded that cohort, confirming the results also in the right-coronary-noncoronary type of BAV.…”
mentioning
confidence: 98%
“…About 10 years ago, having studied the intrinsic stenotic-like kinematics of the echocardiographically normo-functional bicuspid aortic valve (BAV) in magnetic resonance imaging (MRI) examinations, my colleagues and I looked for a method to quantify the restriction of the systolic opening motion of the fused leaflet: 2D true-Fast Imaging with Steady-state Precession (true-FISP) and phase-contrast sequences suggested that conjoint cusp hypomobility, that is, restricted motion in opening phase, was responsible for flow-jet deflection from the vessel's axis [1]. In a small, selected cohort of patients with morphologically and functionally 'homogeneous' BAVs, all right-coronary-left-coronary type, all non-stenotic and non-regurgitant, the cusp opening angle (COA, between the long-axis section of the central part of the fused leaflet and the ventricular-aortic junction plane, in systole), was significantly narrower than in matched tricuspid aortic valve (TAV) of healthy subjects, showing a significant correlation with the yearly aortic growth rate in subsequent prospective follow-up [1], thus proving to be a promising tool for prognostic stratification.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the degree of BAV conjoint cusp opening restriction, which is the mechanism underlying BAVrelated flow eccentricity (6), was measured through a TrueFISP cine-MRI protocol in nonstenotic BAV subjects without aortic dilatation, and quantified by the ''cusp opening angle'' parameter (6). By PC-MRI and computational fluid dynamics models, cusp opening restriction was confirmed to be sufficient as a cause for the deflection of systolic flow jet, independent of the presence of aortopathy.…”
mentioning
confidence: 99%
“…an agreed upon quantitative measure of eccentricity is needed for standardization'': we believe that such agreement should be based on the demonstration of clinical meaningfulness of this quantitative measure. (6) 36 N/A Cusp opening angle Significant independent predictor of aortic diameter and growth rate in the follow-up BAV, bicuspid aortic valve; LV, left ventricle; MMP-2, plasmatic level of matrix metalloproteinase-2; WSS, wall shear stress.…”
mentioning
confidence: 99%